2020
DOI: 10.3892/or.2020.7578
|View full text |Cite
|
Sign up to set email alerts
|

TEAD2 as a novel prognostic factor for hepatocellular carcinoma

Abstract: TEA Domain Transcription Factors (TEADs) are important in development and serve essential roles in tumorigenesis; however, the role of TEAD2 expression in hepatocellular carcinoma (HCC) has not been widely examined. The present study was conducted to investigate the expression status of TEAD2 in HCC and to evaluate whether the expression of TEAD2 is associated with the prognosis of patients with HCC. mRNA expression data was retrieved for Hippo pathway genes of 50 normal control and 377 HCC samples from The Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Previous studies showed that the expression of TEAD2 was enriched in the nucleus and directed a predominant nuclear localization of YAP via the formation of TEAD2-YAP complex in the process of epithelial-mesenchymal transition of breast cancer cells [28]. Besides, the expression of TEAD2 is associated with a poor prognosis in hepatocellular carcinoma patients, which can be considered as a therapeutic target of hepatocellular carcinoma [30]. However, there are little data about the effects of TEAD2 in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the expression of TEAD2 was enriched in the nucleus and directed a predominant nuclear localization of YAP via the formation of TEAD2-YAP complex in the process of epithelial-mesenchymal transition of breast cancer cells [28]. Besides, the expression of TEAD2 is associated with a poor prognosis in hepatocellular carcinoma patients, which can be considered as a therapeutic target of hepatocellular carcinoma [30]. However, there are little data about the effects of TEAD2 in GC.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 TEAD2 was significantly upregulated in hepatocellular carcinoma (HCC) and the higher expression was associated with poor OS time of HCC. 26,27 In addition, TEAD3 could promote the proliferation of gastric cancer cell line MKN-28 through increasing SLC35B4 expression. 28,29 Abnormally expressed TEAD4 could obviously cause epithelial-to-mesenchymal transition (EMT) in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TEAD2, like other members of the TEAD family, can bind to YAP (an important member of the evolutionarily conserved Hippo pathway [ 36 ] and activate the expression of anti-apoptosis and proliferation genes. TEAD2 was considered a new tumor prognostic factor [ 37 ]. Tamm et al [ 38 ] revealed that the Yes-YAP-TEAD2 signaling system was downstream of the LIF signaling pathway, which was of great significance to the self-renewal of mouse ESCs.…”
Section: Discussionmentioning
confidence: 99%